Exploring Gendered Challenges in Accessing Education for Sustainable Development in the Global South: Current Status and Future Directions - Giri, Suja; Baral, Binod; Gharti, Chakra Bahadur; Khanal, Indra Kamal; Shahi, Janak Bahadur; Chaulagai, Krishna Kumari; Thakur, Manju Shree; Pariyar, Om Prakash; Magar, Sapana Gharti; Rana, Subina; Acharya, Sudikshya; Lamsal, Suraj; et al. (Journal of Multidisciplinary Research Advancements, 2026)
Education for Sustainable Development (ESD) is a critical framework for addressing environmental degradation, economic inequality, and social instability, particularly in the Global South. However, systemic barriers—especially gendered disparities—continue to hinder equitable access to ESD. This study systematically reviews gendered challenges in accessing ESD across four Global South contexts: Nepal, Rwanda, Sri Lanka, and Afghanistan. Drawing on Feminist Standpoint Theory, Intersectionality, and the Capability Approach, the analysis examines structural barriers (patriarchal norms, poverty, early marriage), infrastructural deficiencies (lack of menstrual hygiene facilities, geographic isolation, digital divides), policy interventions (Rwanda’s Girls’ Education Policy, Afghanistan’s pre-2021 community-based models), and community-led solutions (Nepal’s Green Schools program). Findings reveal that while Rwanda’s fee elimination achieved high primary enrollment and boosted female participation in STEM. Conversely, Afghanistan’s post-2021 Taliban ban displaced many girls from secondary education, demonstrating the fragility of gains without institutional safeguards. Intersectional analysis shows that Dalit girls in Nepal face discrimination, with many unable to read basic sentences compared to non-Dalit peers. Community-based models like Nepal’s eco-clubs reduced female absenteeism but struggle to scale and reach the most marginalised. The study concludes that sustainable solutions require multi-sectoral collaboration combining policy reform, grassroots engagement, resilient infrastructure, and recognition of girls as active change agents. Investing in gender-equitable ESD is not merely about enrollment targets but about transforming societies toward sustainable futures.